Strong relationship between heart rate deflection point and ventilatory threshold in trained rowers - Mikulic, P.; Vucetic, V.; Sentija, D. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to assess the relationship between heart rate deflection point (HRDP) and ventilatory threshold (VT) to the physiological and performance variables in a relatively large group of trained men rowers. We proposed the hypothesis that physiological and performance variables corresponding to HRDP are not significantly different from corresponding variables at VT, which would justify the use of HRDP as a simple, affordable, and noninvasive method of anaerobic threshold assessment in trained rowers. Eighty-nine trained men rowers (mean ± SD: age 21.2 ± 4.1 years; stature 1.89 ± 0.06 m; body mass 89.2 ± 8.4 kg; Vo2max [maximum oxygen uptake] 5.39 ± 0.62 L/min) completed an incremental rowing ergometer exercise test to exhaustion. Three independent, experienced observers determined both HRDP and VT. HRDP was determined by visual and computer-aided regression analyses and was evident in all rowers. The main findings include (a) there is a strong relationship among all observed physiological and performance variables corresponding to HRHRDP and HRVT (r = 0.79-0.96; p < 0.001) and (b) power output, oxygen uptake, ventilation, tidal volume and breathing rate corresponding to HRHRDP and HRVT were not significantly different (p = 0.011), whereas HRHRDP was slightly but significantly higher than HRVT (174.5 vs. 172.8 beats/min; p = 0.003). The standard error of the estimate in predicting the HRVT based on HRHRDP was 5.1 beats/min. The subsequent data suggest that, in general, trained rowers may be able to periodically assess their aerobic endurance and evaluate the effects of training programs using the HRDP method.